Bacterial Root Microbiome of Plants Growing in Oil Sands Reclamation Covers - Mitter, Eduardo K.; de Freitas, J. Renato; Germida, James J. (Frontiers in Microbiology, 2017)
Oil sands mining in northern Alberta impacts a large footprint, but the industry is committed to reclaim all disturbed land to an ecologically healthy state in response to environmental regulations. However, these newly reconstructed landscapes may be limited by several factors that includes low soil nutrient levels and reduced microbial activity. Rhizosphere microorganisms colonize plant roots providing hosts with nutrients, stimulating growth, suppressing disease and increasing tolerance to abiotic stress. High-throughput sequencing techniques can be used to provide a detailed characterization of microbial community structure. This study used 16S rRNA amplicon sequencing to characterize the bacterial root microbiome associated with annual barley (Hordeum vulgare) and sweet clover (Melilotus albus) growing in an oil sands reclamation area. Our results indicate that Proteobacteria dominated the endosphere, whereas other phyla such as Acidobacteria and Gemmatimonadetes were restricted to the rhizosphere, suggesting that plants have the ability to select for certain soil bacterial consortia. The bacterial community in the endosphere compartments were less rich and diverse compared to the rhizosphere. Furthermore, it was apparent that sweet clover plants were more selective, as the community exhibited a lower richness and diversity compared to barley. Members of the family Rhizobiaceae, such as Sinorhizobium and Rhizobium were mainly associated with clover, whereas Acholeplasma (wall-less bacteria transmitted by insects) was unique to barley. Genera from the Enterobacteriaceae family, such as Yersinia and Lentzea were also mostly detected in barley, while other genera such Pseudomonas and Pantoea were able to successfully colonize both plants. Endophytic bacterial profiles varied within the same plant species at different sampling locations; however, these differences were driven by factors other than slope positions or cover management. Our results suggest that bacterial endophytic communities of plants growing in land reclamation systems are a subset of the rhizosphere community and selection is driven by plant factors.